2016
DOI: 10.1097/mpa.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Endoscopic Ultrasound-Guided Fine-Needle Aspiration Cytology, Carcinoembryonic Antigen, and Amylase in Intraductal Papillary Mucinous Neoplasm

Abstract: Cytology has a limited role because of its lack of sensitivity. Carcinoembryonic antigen modestly differentiated between mucinous and nonmucinous lesions. Amylase did not distinguish IPMNs versus MCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Kromrey et al 121 found no incidence of pancreatic cancer during a 5-year follow-up study of 676 patients with pancreatic cysts. Similarly, Moris et al 37 identified no cases of malignancy among 112 BD-IPMNs with more than 5 years of follow-up. In contrast, Del Chiaro et al 122 reported an IPMN-related mortality of 5.8% after a 10-year follow-up period in patients without highrisk features at baseline.…”
Section: Current Guidelines For Surveillance and Management Of Patienmentioning
confidence: 92%
See 2 more Smart Citations
“…Kromrey et al 121 found no incidence of pancreatic cancer during a 5-year follow-up study of 676 patients with pancreatic cysts. Similarly, Moris et al 37 identified no cases of malignancy among 112 BD-IPMNs with more than 5 years of follow-up. In contrast, Del Chiaro et al 122 reported an IPMN-related mortality of 5.8% after a 10-year follow-up period in patients without highrisk features at baseline.…”
Section: Current Guidelines For Surveillance and Management Of Patienmentioning
confidence: 92%
“…28 Other symptoms that include back pain, weight loss, NOD, and obstructive jaundice are more often associated with malignant transformation of an IPMN but, once again, are not entirely specific. [29][30][31][32]34,35,37,[46][47][48][49][50][51][52] Considering the lack of symptoms in most patients, conventional imaging modalities play a crucial role in the identification of IPMNs and IPMN-associated PDAC, as well as in the detection of a concomitant carcinoma. Here, we discuss the performance of imaging modalities used in the context of cystic lesions; later, we discuss choice of imaging in the context of solid lesions (noncystic PDAC).…”
Section: Diagnostic Methods Of Evaluating Bd-ipmn Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a causative link between IPMN and DM. Of patients with IPMN, 10–45% have diabetes [ 11 14 , 16 , 19 , 31 , 36 , 37 ] and in the case of diabetes, the risk of detecting IPMN is higher (OR 1.79; 95% CI 1.08–2.98) [ 35 ], especially in the case of insulin-use (OR 6.03, 95% CI 1.74–20.84) [ 35 ]. In reverse, the presence of DM is associated with a higher risk of HGD (OR 2.02, 95% CI 1.02–4.01) and carcinoma (OR 2.05, 95% CI 1.08–3.87) [ 38 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Of patients with IPMN, 13–32% are reported to present with secondary acute (recurrent) pancreatitis, although this incidence is based on surgical series and likely to be overestimated. Other symptoms are weight loss, new-onset diabetes, steatorrhea and back pain [ 11 – 15 , 17 – 20 , 31 , 37 , 39 41 ].…”
Section: Diagnosismentioning
confidence: 99%